Co-composting of solid waste and fecal sludge for nutrient and organic matter recovery - Cofie, Olufunke O.; Nikiema, Josiane; Impraim, Robert; Adamtey, Noah; Paul, Johannes G.; Koné, D. (International Water Management Institute, 2016)
Biological treatment, composting, in particular, is a relatively simple, durable and inexpensive alternative for stabilizing and reducing biodegradable waste. Co-composting of different waste sources allows to enhance the compost nutrient value. In particular, integration of ‘biosolids’ from the sanitation sector as potential input material for co-composting would provide a solution for the much needed treatment of fecal sludge from on-site sanitation systems, and make use of its high nutrient content. This research paper elaborates in detail the main parameters that govern the co-composting process as well as factors that control the production of a safe and valuable quality compost. It further explains technological options to tailor the final product to crop and farmer needs.